A Systematic Review of Student Self-Report Instruments that Assess Student-Teacher Relationships. Issue 8 (August 2017) - Phillippo, Kate L.; Conner, Jerusha; Davidson, Shannon; Pope, Denise
Background: A large body of survey-based research asserts that the quality and strength of student-teacher relationships (STRs) predict a host of academic and nonacademic outcomes; however, advances in survey design research have led some to question existing survey instruments' psychometric soundness. Concurrently, qualitative research on STRs has identified important developmental and sociocultural variation in the ways students define, understand, and react to relationships with their teachers. The questions raised by survey methodologists, together with the conceptual elaboration of STRs, suggest that survey instruments used to assess STRs are due for a systematic review. Purpose/Research Questions: This review of survey instruments examines the strengths and shortcomings of existing measures of STRs. Specifically, we ask: How do student self-report survey instruments assess STRs? We examined the extent to which these instruments reflect current survey design principles and existing knowledge about how STRs work, particularly for adolescents. Research Design, Data Collection, and Analysis: A systematic search of peer-reviewed journal articles that (a) focused on North American middle- or high-school students, (b) linked STRs to student outcomes, and (c) used a student-report measure of STRs yielded 66 studies for which we could obtain the full instrument. Instruments were analyzed using a literature-informed protocol and an iterative process that resulted in strong inter-rater agreement. We used tables and matrices to examine patterns, themes, and outliers in our coded data. Findings: The 66 studies varied considerably with respect to how they operationalized STRs and how they addressed the validity of their instruments. Similar survey items were used to measure different constructs, and constructs with the same names were measured inconsistently across studies. Many instruments were limited by (a) items that included words with ambiguous meanings, (b) inconsistent identification of instruments' focal students and teachers across instruments, and (c) the use of negatively worded items to measure STRs' strength. Conclusions and Recommendations: If STR research is to meet its promise to guide and inform teachers' efforts to develop and sustain effective relationships with their students, the field needs to properly identify those behaviors that make a difference for different students and those that do not. The next generation of student-report STR survey instruments requires more stringent attention to construct specification and validity, as well as to item generation (specifically, language use), in order to most effectively measure and identify aspects of STRs that affect student performance and well-being.